Dual Erb B Inhibition in Oesophago-gastric Cancer (DEBIOC): A phase I dose escalating safety study and randomised dose expansion of AZD8931 in combination with oxaliplatin and capecitabine chemotherapy in patients with oesophagogastric adenocarcinoma. (January 2020) - Thomas, Anne; Virdee, Pradeep S.; Eatock, Martin; Lord, Simon R.; Falk, Stephen; Anthoney, D. Alan; Turkington, Richard C.; Goff, Matthew; Elhussein, Leena; Collins, Linda; Love, Sharon; Moschandreas, Joanna; et al.
Abstract: Background: AZD8931 has equipotent activity against epidermal growth factor receptor, erbB2, and erbB3. Primary objectives were to determine the recommended phase II dose (RP2D) of AZD8931 + chemotherapy, and subsequently assess safety/preliminary clinical activity in patients with operable oesophagogastric cancer (OGC). Methods: AZD8931 (20 mg, 40 mg or 60 mg bd) was given with Xelox (oxaliplatin + capecitabine) for eight 21-day cycles, continuously or with intermittent schedule (4 days on/3 off every week; 14 days on/7 off, per cycle) in a rolling-six design. Subsequently, patients with OGC were randomised 2:1 to AZD8931 + Xelox at RP2D or Xelox only for two cycles, followed by radical oesophagogastric surgery. Secondary outcomes were safety, complete resection (R0) rate, six-month progression-free survival (PFS) and overall survival. Results: During escalation, four dose-limiting toxicities were observed among 24 patients: skin rash (1) and failure to deliver 100% of Xelox because of treatment-associated grade III-IV adverse events (AEs) (3: diarrhoea and vomiting; vomiting; fatigue). Serious adverse events (SAE) occurred in 15 of 24 (63%) patients. RP2D was 20-mg bd with the 4/3 schedule. In the expansion phase, 2 of 20 (10%) patients in the Xelox + AZD8931 group and 5/10 (50%) patients in the Xelox group had grade III–IV AEs. Six-month PFS was 85% (90% CI: 66%–94%) in Xelox + AZD8931 and 100% in Xelox alone. Seven deaths (35%) occurred with Xelox + AZD8931 and one (10%) with Xelox. R0 rate was 45% (9/20) with Xelox + AZD8931 and 90% (9/10) with Xelox-alone ( P = 0.024). Conclusion: Xelox + AZD8931 (20 mg bd 4/3 days) has an acceptable safety profile administered as neoadjuvant therapy in operable patients with OGC. (Trial registration: EudraCT 2011-003169-13, ISRCTN-68093791). Highlights: First study to assess safety and tolerability of the novel pan erbB inhibitor AZD8931 in oesophagogastric cancer (OGC). Recommended phase II dose schedule determined to be 20-mg bd for 4 days on/3 days off, per cycle. Feasibility of adding novel targeted therapies to standard-of-care for oesophago-gastric cancer is confirmed.